Contextualizing The Value Of Islamic Education In The Digital Era: Challenges And Adaptations In The Khitbah Hadith - Taufik, Akhmat; Kasman, Kasman; Wibowo, Safrudin Edi; Hosaini, Hosaini; Khaleel, Amal Hameed (Institut Agama Islam An-Nawawi Purworejo, 2024)
This study aims to examine the values of Islamic education contained in the khitbah hadith and its relevance in the digital era. The transformation of technology and social media in the digital era has changed the way individuals interact, including in the marriage proposal process. This study uses a qualitative method based on library research to explore the adaptation of the educational values of the khitbah hadith in facing digital challenges. The results of the study identified the main educational values in the khitbah hadith, namely maintaining intentions and goals, honor and modesty, openness, avoiding immorality, not interfering with other people's khitbah, careful consideration, and joint family decisions. In the digital context, these values are contextualized into maintaining intentions and integrity on digital platforms, using technology wisely, maintaining sharia restrictions in virtual spaces, and increasing openness and transparency through technology. This research has important implications in providing practical guidance for young Muslims to manage pre-marital interactions and relationships while adhering to the values of Islamic education in the digital era. In addition, this research also provides insights for Islamic educators, scholars and practitioners to develop learning materials that are relevant to the current digital situation, as well as integrating technology in Islamic education that is able to maintain and strengthen the values of Sharia. Thus, the values in the khitbah hadith can become an ethical foundation in responding to modern challenges without abandoning Islamic principles.